Managing older medical patients in hospital: a study of the outcomes from a shift of resources to the 'front door'. Issue 3 (2016) - Tiwari, Divya; Vassallo, Michael; Owen, Charlotte; Renaut, Richard; Allen, Stephen
No abstract available